Hydroallantois in a Gir Cow: A Case Report - Bharai, Munja J.; Dodiya, Vivek A. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Hydroallantois is a pathological condition characterized by excess accumulation of allantoic fluid in the allanatois during fetal development. Usually, maternal factors are involved, where rapid and abnormal distension of the abdomen occurs (Drivers Peek, 2008). If the case is not diagnosed and treated early and the animal cannot rise, the prognosis is poor. In dairy cattle, hydroallantois is more common in the last phase of the third trimester and less so in buffaloes and heifers (Kumar et al., 1988; Srinivas and Sreenu, 2006). The physiopathology of hydroallantois reduces placental vascularization resulting in metabolic changes in the placental tissue and fetal membranes, thereby accumulating fetal fluids (Kapadiya et al., 2018).